Analisis Prinsip Desain Dalam Menciptakan Suasana Naratif Pada Buku ‘Fabel Nusantara : Asal Mula Pesut Mahakam’ - Naziha Nur Afifah; Raden Hadapiningrani Kusumohendrarto (Universitas Dian Nuswantoro, 2026)
The study aims to analyze the application of design principles, color theory, and typography to create a narrative atmosphere in the children's book of the Fabel Nusantara: Asal Mula Pesut Mahakam. This study used a descriptive qualitative method with a visual analysis approach to illustrations, design composition, color schemes, and typographical characters used in books. Analysis results show that applying design principles such as balance, visual unity, and contrast can help direct the reader's focus and clarify the storyline. The use of natural nuanced colors with warm and cold color temperatures plays a role in building the emotional atmosphere of the story that is in line with the psychological development of the child. In addition, sans-serif typography with rounded and easy-to-read characters supports text readability and strengthens the friendly impression for child readers. Overall, the integration of design principles, colors, and typography in the book proved effective in building a narrative atmosphere and strengthening the moral message of folklore to children.